An algorithmic approach to soft-tissue reconstruction around the knee using anterolateral thigh perforator flap in patients with post-traumatic knee osteomyelitis - Jeong, Seong-Ho; Baik, Seung-Hee; Namgoong, Sik; Dhong, Eun-Sang; Han, Seung-Kyu (Frontiers in Surgery, 2023)
Background: Free tissue transfer to the knee region in patients with chronic post-traumatic knee osteomyelitis (CTKOM) poses a great challenge to surgeons because the remaining soft tissues adjacent to defects, including vascular structures, are usually damaged by chronic inflammation and multiple debridements. Thus, we developed an algorithm to help select the optimal recipient vessels and appropriate anterolateral thigh perforator (ALTP) flap type. Further, we performed surgery using this algorithm and achieved successful reconstructions. This study aims to review our experiences in algorithmic reconstruction and assess its efficacy. Methods: According to the defect’s size and location, our algorithm suggested one of three ALTP flap types, including regular oval-shaped flap with central perforators (RO-Cen-ALTP flap), long oval-shaped flap with central perforators (LO-Cen-ALTP flap), and long oval-shaped flap with eccentric perforators (LO-Ecc-ALTP flap). Besides, through the algorithm, one recipient vessel was selected among three candidates, including descending branch of the lateral circumflex femoral artery (DB-LCFA), anterior tibial artery (ATA), and posterior tibial artery (PTA). Based on this algorithmic decision, we performed individualized soft tissue reconstructions of the knee in 21 patients with CTKOM, between March 2013 and June 2021. The medical records of the patients were retrospectively reviewed. Results: The RO-Cen-ALTP flap (n=9) and ATA (n=9) were the most commonly used for reconstruction. The RO-Cen-ALTP flap anastomosed to the ATA was most commonly selected (n=4) using the algorithm, followed by the RO-Cen-ALTP flap anastomosed to the DB-LCFA (n=3), and the LO-Cen-ALTP flap anastomosed to the ATA (n=3). All transferred ALTP flaps survived the follow-up period. Postoperative venous congestion in two patients and hematoma in one patient were resolved by immediate treatment. The postoperative course was uneventful. Conclusion: During free ALTP flap transfer to CTKOM-related knee defects, we could select the optimal recipient vessel and appropriate flap type using our algorithm and obtain excellent reconstructive outcomes. Therefore, we believe that our algorithm could provide helpful guidance to reconstructive surgeons on free ALTP flap transfer to reconstruct CTKOM-related soft tissue defects.